Assessing Australian women's knowledge and knowledge preferences about long-term health after hypertensive disorders of pregnancy: a survey study. Issue 12 (17th December 2020) - Roth, Heike; Homer, Caroline S E; LeMarquand, Grace; Roberts, Lynne M; Hanley, LIsa; Brown, Mark; Henry, Amanda
Abstract : Objectives: To (1) assess women's current knowledge regarding long-term cardiovascular health after hypertensive disorders of pregnancy (2) elicit women's preferred educational content and format regarding health after hypertensive disorders of pregnancy. Design and setting: A custom-created online survey exploring Australian women's knowledge about long-term health after hypertensive disorders of pregnancy, distributed through consumer groups and social media. Participants: 266 women with (n=174) or without (n=92) a history of hypertensive disorders of pregnancy. Primary and secondary outcome measures: (1) Proportion of women identifying long-term health risks after hypertensive disorder of pregnancy using a 10-point risk knowledge score with 0–4 'low', 4.1–7.0 'moderate' and 7.1–10 'high'. (2) Exploration of preferred content, format and distribution of educational material post hypertensive disorder of pregnancy. Results: Knowledge scores about health after hypertensive disorder of pregnancy were moderate in groups with and without a history of the disorder. Knowledge was highest regarding risk of recurrent hypertensive disorders in a subsequent pregnancy, 'moderate' for chronic hypertension and heart attack, 'moderate' and 'low' regarding risk of heart disease and 'low' for diabetes and renal disease. Only 36% of all participants were aware that risks start within 10 years after the affected pregnancy. The majority of respondents with a history of hypertensive disorder of pregnancy (76%) preferred receiving information about long-term health 0–6 months post partum from a healthcare provider (80%), key organisations (60%), social media (47%) and brochures/flyers (43%). Conclusions: Women's knowledge regarding health risks after hypertensive disorder of pregnancy was 'moderate', although with important disease-specific gaps such as increased risk of diabetes. Most women wanted to be informed about their long-term health from a healthcare provider.